Tackling society's grand challenges with design science : 11th International Conference, DESRIST 2016, St. John's, NL, Canada, May 23-25, 2016, Proceedings /: 11th International Conference, DESRIST 2016, St. John's, NL, Canada, May 23-25, 2016, Proceedings. (2016) - Unknown
No abstract available